2012
DOI: 10.1021/bi3000947
|View full text |Cite
|
Sign up to set email alerts
|

Weak Interactions between Folate and Osmolytes in Solution

Abstract: Previous osmotic stress studies on the role of solvent in two structurally unrelated dihydrofolate reductases (DHFRs) found weaker binding of dihydrofolate (DHF) to either enzyme in the presence of osmolytes. To explain these unusual results, weak interactions between DHF and osmolytes were proposed, with a competition between osmolyte and DHFR for DHF. High osmolyte concentrations will inhibit binding of the cognate pair. To evaluate this hypothesis, we devised a small molecule approach. Dimerization of folat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
40
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(48 citation statements)
references
References 46 publications
5
40
1
Order By: Relevance
“…Once metabolites are bound on the surface of a macromolecule, diffusion becomes two-dimensional and slows down considerably as illustrated in detail for ATP and valine (Figure 6C; Video 4). Trapping of metabolites on macromolecular surfaces reduces the effective concentration of freely-diffusing metabolites consistent with recent experiments that have inferred a large fraction of surface-interacting metabolites due to crowding (Duff et al, 2012). A recent analysis of absolute metabolite concentrations in E. coli has found that most concentrations were above the values of the Michaelis constant K m for enzymes binding those metabolites (Bennett et al, 2009).…”
Section: Resultssupporting
confidence: 86%
“…Once metabolites are bound on the surface of a macromolecule, diffusion becomes two-dimensional and slows down considerably as illustrated in detail for ATP and valine (Figure 6C; Video 4). Trapping of metabolites on macromolecular surfaces reduces the effective concentration of freely-diffusing metabolites consistent with recent experiments that have inferred a large fraction of surface-interacting metabolites due to crowding (Duff et al, 2012). A recent analysis of absolute metabolite concentrations in E. coli has found that most concentrations were above the values of the Michaelis constant K m for enzymes binding those metabolites (Bennett et al, 2009).…”
Section: Resultssupporting
confidence: 86%
“…76 We have also used nuclear magnetic resonance to observe interactions between folate and osmolytes (middle column, green equilibrium arrows). 15 Both sets of results are consistent with this model.…”
supporting
confidence: 71%
“…Homonuclear ( 1 H) nuclear Overhauser effect spectroscopy (NOESY) experiments found NOEs between the protons on the C7 atom of folate and protons on the C9 and C3′/C5′ atoms, and between the C9 proton and the C3′/C5′ protons (see Figure S1 for the structure and atom numbering of folate). 15 However, a change in sign for the NOE between the C9 and C3′/C5′ protons from positive (without betaine) to negative (with betaine) was observed. The change in the sign for the NOE suggested a slower rotational rate for the p- amino-benzoyl ring protons, indicative of an interaction between betaine and this ring.…”
mentioning
confidence: 96%
See 2 more Smart Citations